De Middelheim Collectie - Meewis, Menno; Middelheimmuseum, Antwerpen (Antwerpen : Ludion Gent Middelheimmuseum Antwerpen, 2010)
Gentils, Vic ; Wouters, Rik ; Moore, Henry ; Etienne-Martin ; Geys, Jef ; Bourdelle, Emile-Antoine ; Rodin, Auguste ; Bill, Max ; Rogiers, Peter ; Lipchitz, Jacques ; Manzu, Giacomo ; Maillol, Aristide ; Arp, Hans (Jean) ; Gargallo, Pablo ; Duchamp-Villon, Raymond ; Graham, Dan ; Laurens, Henri ; Couturier, Robert ; Kolbe, Georg ; Dodeigne, Eugène ; Meunier, Constantin ; Chadwick, Lynn ; McCorkle, Corey ; Bodmer, Walter ; Milles, Carl ; Van Breedam, Camiel ; Van Sumere, Hilde ; Hellgren, Ingmar ; Heck, Kati ; Marini, Marino ; Wotruba, Fritz ; Hepworth, Barbara ; Armitage, Kenneth ; Pompon, François ; Visch, Henk ; Renoir, Auguste ; Permeke, Constant ; Zadkine, Ossip ; Varga, Imre ; D'Haese, Roel ; Nevelson, Louise ; Burden, Chris ; Rosenthal, Bernard ; King, Phillip ; Calder, Alexander ; Soto, Jesus Rafael ; Chirino, Martin ; Dubon, Jorge ; Janssens, Ann Veronica ; Deleu, Luc ; Cabrita Reis, Pedro ; Atelier van Lieshout ; Genzken, Isa ; Panamarenko ; Visch, Henk ; Cragg, Tony (Anthony) ; Vandenhove, Charles ; Mullican, Matt ; d'O, Honoré ; Kirkeby, Per ; Ulrichs, Timm ; Bijl, Guillaume ; Stockholder, Jessica ; Lohaus, Bernd ; Klingelhöller, Harald ; Vermeiren, Didier ; Copers, Leo ; Fabro, Luciano ; Schütte, Thomas ; West, Franz ; Muñoz, Juan ; Andre, Carl
Nederlands
boek